The Influence of Service Quality and Trust on User Loyalty through User Satisfaction DANA in Jakarta - Sari, Annisa; Usman, Osly (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The rapid pace of technology has produced a new innovation in financial matters, namely Financial Technology, which has also given rise to something new, namely digital transactions or e-wallets. The aim of this research is to determine the effect of service quality and trust on user loyalty through DANA user satisfaction in Jakarta. This research uses quantitative methods with a research population of 100 people and data collection techniques using questionnaires. The sampling technique used was purposive sampling. Data analysis in this research uses the help of SmartPLS 4. The results of the research are that service quality has a positive and insignificant influence on user loyalty, there is a positive and significant influence between service quality and user satisfaction, there is a positive and significant influence between trust and user loyalty, there is positive and significant influence between trust and user satisfaction, the influence between user satisfaction and user loyalty is positive and not significant, service quality through user satisfaction has a positive and not significant influence on user loyalty, and trust and user loyalty through user satisfaction is positive and not significant.